Monitoring temperature patterns at selected world heritage sites in Egypt using high resolution WorldClim data - Viranch N. Dave (Acta Geographica Debrecina Landscape & Environment series, 2023)
Long term temperature patterns helps in assessing changes in the climatic conditions of an area and climatic changes poses a major challenge to the world heritage sites whether it is natural or cultural. Therefore in this study using maximum and minimum temperature data for the period 1960-2021 downloaded from WorldClim 2.1 calculation of mean temperature is done in QGIS environment for the selected UNESCO world heritage sites of Arab Republic of Egypt. WorldClim 2.1 provides finer resolution gridded data downscaled from Climate Research Unit. Trend analysis using linear regression and Mann-Kendall method and Sen’s Slope estimate is used to understand the patterns of mean temperature at all the selected sites. The study reveals that mean temperature at all the selected sites is increasing but since 1990 the sites which are located geographically in lower Egypt are witnessing rapid increase in mean temperature compared to the sites located in upper Egypt which historically witnessed more temperature due to its geographical milieu. This study can help in stimulating the utility of geospatial data in understanding the changes in climatic parameters in relation to world heritage sites. Moreover it can serve as foundation upon which detailed longitudinal site specific investigation can be done.